HUBUNGAN PENGETAHUAN TENTANG BAHAYA PESTISIDA, PENDIDIKAN DAN SIKAP DENGAN PRAKTIK PENGGUNAAN ALAT PELINDUNG DIRI (APD) PADA PETANI BAWANG MERAH - Wiwi Yuliyana; Wulandari Meikawati (Universitas Muhammadiyah Semarang, 2015)
Background: Pesticides can cause negative or positive to the human health and the environment. The using pesticides will give negative effects to the human health and the environment either directly or indirectly. Red onion farmer is a profession whose high risk the using of pesticides, but most of them are rarely applied self protection. In order to protect human and environment from negative effects, the effort of complete self protection (APD) is very needed. Objective: Know the correlation of knowledge, education, attitude with practice of the use self protection (APD) on onion farmers. Methods: The typeof research used is observational analytic with the approach Cross sectional freevariables is the knowledge about the dangers of pesticides, education, attitude and practice is variable use of self protection (APD). The sample of this research is citizen who worked as farmers with simple random sampling technique with a large sample of 41 respondents. Using the Chi-square analysis. Results: Based on 41 respondents, 24 (58.5%) knowledgeable about the dangers of pesticides. Education respondents, 39 (95.2%) of respondents is low educated. There are 22 respondents (53.7%) does not support the use of the personal protection attitude of complete. The practice of the use self protection (APD), 39 reponden (95,1%) not use of complete self protection (APD). Conclusion: There is no correlation between knowledge about the dangers of pesticides with the practice of the use of personal protection (p=0.512), there is no correlation between education with the practice of the use of personal protection (p=1.000), there is no correlation between attitude with practice of the use of personal protection (p=1.000).